(untitled) (Research, Society and Development, 2024)
This research aims to identify students’ perspectives on their ideal English professor, characteristics and skills and investigate whether they would like to learn a second language and consider it to aid their professional life. Therefore, a survey was done online with N= 220 learners taking the A1 English level in a public university in the coastal region of Ecuador. The data collected comprised 19 statements divided into three categories ( 1. The perspective in the English professor’s Identity; (2. Perspectives on the English Professor’s Instruction; (3. Teachers Profile. The analysis uses descriptive statistics. The results demonstrate that students prefer flexible English professors who motivate them to learn a second language, which is essential for them. Most of the students agree that the ideal English professor must have a good proficiency in English level and studied in the field. In summary, as students like to learn a second language, believing it is essential for their professional career, they would prefer a professor who adapts to their necessities.